Evaluation of knowledge of HIV pre-exposure prophylaxis among Medical students at the University of Vassouras-RJ (Research, Society and Development, 2024)
Objective: To investigate medical students' knowledge about HIV pre-exposure prophylaxis (PrEP). Methodology: An analysis was carried out with the answers of 290 students from the University of Vassouras, in the state of Rio de Janeiro, enrolled in the periods from the first to the twelfth. The answers were collected during the second academic period of 2023, through an electronic form with 12 questions, made available via Google Forms, accompanied by a Free and Informed Consent Form. The project was previously submitted to Plataforma Brasil and to the institutional ethics committee, obtaining approval under opinion 5.966.511. Results: Analyzing the performance according to the academic cycle, in the basic cycle of the 127 participants, 62.2% of them had